Impacts of prenatal nanomaterial exposure on male adult Sprague-Dawley rat behavior and cognition. Issue 11 (2nd June 2016) - Engler-Chiurazzi, Elizabeth B.; Stapleton, Phoebe A.; Stalnaker, Jessica J.; Ren, Xuefang; Hu, Heng; Nurkiewicz, Timothy R.; McBride, Carroll R.; Yi, Jinghai; Engels, Kevin; Simpkins, James W.
ABSTRACT: It is generally accepted that gestational xenobiotic exposures result in systemic consequences in the adult F1 generation. However, data on detailed behavioral and cognitive consequences remain limited. Using our whole-body nanoparticle inhalation facility, pregnant Sprague-Dawley rats (gestational day [GD] 7) were exposed 4 d/wk to either filtered air (control) or nano-titanium dioxide aerosols (nano-TiO2 ; count median aerodynamic diameter of 170.9 ± 6.4 nm, 10.4 ± 0.4 mg/m 3, 5 h/d) for 7.8 ± 0.5 d of the remaining gestational period. All rats received their final exposure on GD 20 prior to delivery. The calculated daily maternal deposition was 13.9 ± 0.5 µg. Subsequently, at 5 mo of age, behavior and cognitive functions of these pups were evaluated employing a standard battery of locomotion, learning, and anxiety tests. These assessments revealed significant working impairments, especially under maximal mnemonic challenge, and possible deficits in initial motivation in male F1 adults. Evidence indicates that maternal engineered nanomaterial exposure during gestation produces psychological deficits that persist into adulthood in male rats.